2019
DOI: 10.1002/jia2.25227
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dolutegravir‐based regimens as either first‐line or switch antiretroviral therapy: data from the Icona cohort

Abstract: IntroductionConcerns about dolutegravir (DTG) tolerability in the real‐life setting have recently arisen. We aimed to estimate the risk of treatment discontinuation and virological failure of DTG‐based regimens from a large cohort of HIV‐infected individuals.MethodsWe performed a multicentre, observational study including all antiretroviral therapy (ART)‐naïve and virologically suppressed treatment‐experienced (TE) patients from the Icona (Italian Cohort Naïve Antiretrovirals) cohort who started, for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 26 publications
6
41
2
Order By: Relevance
“…However, to date, the rate of discontinuation of DTG-based therapies for NP-AEs has not been confirmed in a uniform way. Ours (3.9%) is concordant with those reported in some real-life studies, 17-25 which ranged between 1.7% and 5.6%. In contrast, this rate was significantly higher in 2 cohorts 7,8 (8.3% and 9.9%) and lower in the other 2, with only 0.6% and 0.7% of the patients having to stop DTG because of NP-AEs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, to date, the rate of discontinuation of DTG-based therapies for NP-AEs has not been confirmed in a uniform way. Ours (3.9%) is concordant with those reported in some real-life studies, 17-25 which ranged between 1.7% and 5.6%. In contrast, this rate was significantly higher in 2 cohorts 7,8 (8.3% and 9.9%) and lower in the other 2, with only 0.6% and 0.7% of the patients having to stop DTG because of NP-AEs.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of AEs identified in our study was high (42.2%), with an incidence of interruptions for this reason of 8.7% at W48 (13.6% and 7.6% in ART-naive and TE patients, respectively). Our rates of AEs leading to DTG/ABC/3TC discontinuation were higher than those reported in clinical trials with DTG 1-6 (which ranged between 2.0% and 4.0% within the first year), but also in the CoRIS 15 and ICONA 17 cohorts, which reported an incidence of 3.6 and 3.9%, respectively. In contrast, the rate reported in the TRIUMPH Cohort 16 was closer to ours, with an incidence of interruptions caused by AEs of 6.9%.…”
Section: Discussioncontrasting
confidence: 75%
“…Furthermore, a short duration of 3 months of viral suppression seen as against one-year or longer duration to a achieve reasonable viral suppression with other combinations is in agreement of earlier ndings of Rhangale and colleagues (21). similarly, Annalisa and colleagues have reported the clinical e cacy and tolerability of DTG-based regimen (22). This will prevent the possible development of resistance as seen with other combinations.…”
Section: Discussionmentioning
confidence: 96%
“…This result agrees with other studies, 22 , 23 which reported high treatment satisfaction with dolutegravir based regimen. This higher treatment satisfaction with dolutegravir based regimen could be due to the reason that dolutegravir based regimen is more effective, 24 easier to use, and has fewer side effects 25 than alternative drugs that are currently used. This can also partially be explained by the fact that dolutegravir reduces pill burden and its simplification which allows once-daily administration, 26 which in turn increases treatment satisfaction.…”
Section: Discussionmentioning
confidence: 99%